INFORMATION MAPS ON PLATFORMS - AS A TOOL FOR DEVELOPING THE ENTREPRENEURIAL ABILITY OF THE POPULATION (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article analyzes the prospects of using information maps integrated into business platforms that provide an environment of economic transparency in increasing the level of economic literacy and entrepreneurship of the population, the socio-economic role and importance of the map in attracting the population to entrepreneurship and supporting entrepreneurship. Also, in order to scientifically substantiate the efficiency levels of information maps, their function of mutually integrating endogenous and exogenous factors that create an entrepreneurial environment and increase the entrepreneurial ability of the population is highlighted, and in order to ensure employment and development in the regions, real-time and actual regional opportunities (taxes, subsidies, A proposal to apply the reflection approach is put forward.
Keywords: Entrepreneurship, economic literacy, entrepreneurial ability, information platforms, stages of entrepreneurship, factors affecting the development of entrepreneurship, endogenous factor, exogenous factor, business environment.